2013
DOI: 10.1016/j.geoderma.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fire and post-fire management techniques on soil chemical properties

Abstract: The effects of fire (Control burned soil) and two emergency stabilisation techniques (grass Seeding and straw Mulching) on 20 chemical characteristics were evaluated on 0-5 cm top-soils sampled 1, 90, 180 and 365 days after an experimental fire in a steep shrubland of a temperate-humid region (NW Spain). Most part of pH (in H 2 0 and KC1) variance was explained by the sampling date. No clear temporal trends were identifiable for total soil C and N content, likely due to the large SOM pool in these soils; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
45
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 59 publications
14
45
4
Order By: Relevance
“…As confirmed by the two way ANOVA test, fire had no significant effect on the available Mn contents of the 0-5 and 10-15 cm soil layers, although Gomez-Rey et al 29 reported higher post-fire Mn availability in the 0-5 cm soil layer, attributed to Mn supplied by ashes from the burned vegetation. In contrast to the lack of difference in terms of the Mn availability between the burned and unburned areas in the 0-5 and 10-15 cm soil layers, the 5-10 cm soil layer showed a significant post-fire decrease in the available Mn compared with the unburned areas.…”
Section: Competing Interestsmentioning
confidence: 70%
See 3 more Smart Citations
“…As confirmed by the two way ANOVA test, fire had no significant effect on the available Mn contents of the 0-5 and 10-15 cm soil layers, although Gomez-Rey et al 29 reported higher post-fire Mn availability in the 0-5 cm soil layer, attributed to Mn supplied by ashes from the burned vegetation. In contrast to the lack of difference in terms of the Mn availability between the burned and unburned areas in the 0-5 and 10-15 cm soil layers, the 5-10 cm soil layer showed a significant post-fire decrease in the available Mn compared with the unburned areas.…”
Section: Competing Interestsmentioning
confidence: 70%
“…Some recent studies have also reported a decline in the Fe availability of burned soils 18,29,[66][67][68] . The fire induced depletion of the available Fe in the burned area could be associated with losses (by convection in smoke columns, transport by wind, erosion and leaching) and/or conversion to insoluble oxidized forms in soils as have been reported for several other nutrients 25,69 .…”
Section: Competing Interestsmentioning
confidence: 95%
See 2 more Smart Citations
“…In agreement with the findings of other authors, results showed that our burned soil had: a) higher soil pH and electrical conductivity, due to the oxides and carbonates of basic ions supplied by ashes and the combustion of organic acids, that lead to increased extractable Na, Ca and P (see, for example, the review by Certini, 2005); b) lower contents of soil C and N, due to volatilization (Certini 2005), and also lower values of soil d 15 N, related with the deposition of 15 N-depleted charred materials from N 2 -fixing legumes and/or ectomycorhized ericaceous (Gómez-Rey et al 2013b); and c) lower levels of Fe and higher of Mn (Certini 2005;García-Marco and González-Prieto 2008;Close et al 2011;Gómez-Rey et al 2013a). Contrastingly, although several authors reported that fire increases the availability of K, Mg, Zn and Cu in soils (Certini 2005;García-Marco and González-Prieto 2008;Close et al 2011;Gómez-Rey et al 2013a), we did not find a significant effect on these nutrients.…”
Section: Discussionmentioning
confidence: 99%